Anger, Coping, and Affective Temperament in Opioid-Dependent Men: A Controlled Study - Gıynaş Ayhan, Medine; Öztürk, Ali Hakan; Seven, Hilal; Kırcı Ercan, Seda; Eren, İbrahim (Addicta: The Turkish Journal on Addictions, 2021)
This study aimed to investigate the anger levels, coping strategies, and affective temperaments of men with opioid dependence compared with a control group. The study included 50 male outpatients with opioid dependence who had completed the detoxification process. A total of 50 men who matched the study group in terms of age, sex, and education level were included as the control group. The state trait anger expression scale; coping inventory; and temperament evaluation of Memphis, Pisa, Paris, and San Diego auto questionnaire scales were completed by all the participants. The trait anger, anger-in, and anger-out scores of the case group were significantly higher than those of the control group. Cyclothymic and hyperthymic temperament scores were significantly higher in the case group. In the case group, mental disengagement, focus on and venting of emotions, and behavioral and alcohol-drug disengagement scores were significantly higher. The patients in the case group were also less likely to use humor, emotional and social support, and planning. In conclusion, a higher level of anger in opioid-dependent men was observed with the use of dysfunctional methods to cope with stress and hyperthymic and cyclothymic temperament properties compared with the control group. Treatment planning for anger-control, affective temperaments, and coping strategies are likely to help in a positive prognosis.